Validating the instrument of study anxiety sources using factor analysis - Vitasari, Prima; Muhammad Nubli, Abdul Wahab; Herawan, Tutut; Ahmad, Othman; Suriya Kumar, Sinnadurai (Elsevier, 2011)
Anxiety can be referred as an underlying source of students’ fears during their study process. Several researches have proposed and identified the anxiety sources among students. However, not many proposals are concerned on validating the instrument of study anxiety sources. In this paper, the validation of the instrument of study anxiety sources is described. For identifying study anxiety sources, a total 300 students of University Malaysia Pahang (UMP) participated in this survey during second semester in the academic year 2008/2009. Findings from 7 dimensions in identifying of study anxiety sources show that all items had achieved validity as analysed by factor analysis. These sources are exam anxiety, presentation anxiety, mathematics anxiety, language anxiety, social anxiety, family anxiety, and library anxiety. Since, the Cronbach alpha of reliability was acceptable, it can be concluded that the associations of students feeling, thought, and experiences toward study anxiety sources support the validity of the instrument.